2005
DOI: 10.1063/1.1862752
|View full text |Cite
|
Sign up to set email alerts
|

Current bursts in lipid bilayers initiated by colloidal quantum dots

Abstract: Inorganic semiconductor nanocrystals, also called quantum dots, have recently attracted considerable interest as fluorescent labels. We report that CdSe QDs initiate current bursts in lipid bilayer membranes upon application of a bias voltage. The current bursts observed resemble those produced by the peptaibol class of antibiotics such as alamethicin and trichorzins. The current fluctuations are dependent on the bias voltage and on the concentration of the quantum dots applied to the membrane. Our data sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The only previous electrophysiological studies, to our knowledge, show that also CdSe quantum dots of 3À15 nm diameter cause current bursts of up to 800 pA (8 nS) in DOPC-containing bilayers and channel-like current spikes of up to 30 pA (0.6 nS) in more rigid bilayers of diphytanoyl phosphatidylcholine. 26,27 Additionally, Chen et al recently demonstrated that ARTICLE various cationic polymer nanoparticles (∼5À8 nm diameter) gradually increase the conductance of cell membranes, with occasional discrete current steps of up to 0.9 ( 1.2 nA, as measured by patch-clamp electrophysiology of living cells. 28 A key difference with these polymeric nanoparticles and quantum dots is the larger diameter and the larger variation in diameter of the silica nanospheres investigated here.…”
Section: Resultsmentioning
confidence: 99%
“…The only previous electrophysiological studies, to our knowledge, show that also CdSe quantum dots of 3À15 nm diameter cause current bursts of up to 800 pA (8 nS) in DOPC-containing bilayers and channel-like current spikes of up to 30 pA (0.6 nS) in more rigid bilayers of diphytanoyl phosphatidylcholine. 26,27 Additionally, Chen et al recently demonstrated that ARTICLE various cationic polymer nanoparticles (∼5À8 nm diameter) gradually increase the conductance of cell membranes, with occasional discrete current steps of up to 0.9 ( 1.2 nA, as measured by patch-clamp electrophysiology of living cells. 28 A key difference with these polymeric nanoparticles and quantum dots is the larger diameter and the larger variation in diameter of the silica nanospheres investigated here.…”
Section: Resultsmentioning
confidence: 99%
“…1(a). The streptavidin-linked magnetite (Fe 3 O 4 ) nanoparticles (fluidMAG-Streptavidin, purchased from Chemicell GmbH), with an average diameter of ß100 nm [full width at half Earlier experiments have shown that an oligomeric aggregation of quantum dots on the surface of suspended bilayers forms ion-conducting nanopores [10,11]. In the present case, while undergoing Brownian motion in the buffer solution, due to thermomechanical diffusion, a number of aligned MNPs would hit the impermeable bilayer under a static magnetic field (SMF).…”
Section: Experiment: Materials and Methodsmentioning
confidence: 99%
“…29,30 For example, electrical measurements of ENM-exposed suspended bilayers have shown that quantum dots, carbon nanotubes and polystyrene or silica nanospheres render bilayers permeable to ions, indicating a nanoparticle-induced perturbation of the bilayer structure. [31][32][33][34][35] It has also been visualized with atomic force microscopy that cationic dendrimers and silica nanospheres can create holes in mica-supported bilayers, 36 and fluorimetry measurements have demonstrated that titanium dioxide and silica nanospheres, cationic and anionic gold nanoparticles and protein-coated carbon nanotubes are all able to induce the release of fluorescent dyes from lipid vesicles. [37][38][39][40] But because most studies only concern a small number of ENM species, structure-function relationships remain elusive.…”
Section: Introductionmentioning
confidence: 99%